Improving human performance in flight operations using augmented reality and quick coherence technique - Zhang, Jingyi (Cranfield University, 2023)
Human errors continuously play a major role in the root cause of air accidents, which brings up the need for effective improvements in pilots’ human performance during flight operations. This research addresses two main challenges of pilots’ interface to improve the non-technical performance in flight operations from a system human factors perspective. The first part is related to the human-computer interaction considerations in modern flight decks. An innovative augmented reality (AR) interactive checklist is developed. This AR application blends the virtual holographic checklist and augmented guiding cues within the flight deck and allows multiple input modes of gesture and voice. Compared to the traditional paper-based pre-landing checklist, the voice-command AR can improve cognitive information processing during landing operations. The voice input modality of AR provides a more intuitive and flexible interface to improve human-computer interaction effectiveness. It is also well-applicable in multitasking flight scenarios compared to the gesture-command interaction. In the second part, the interface between pilots and the societal environment is investigated. The quick coherence technique (QCT) training is applied to address the negative impacts on pilots’ psychological health and cognitive performance during the COVID-19 pandemic. The QCT is based on paced breathing exercises and heart rate variability biofeedback. Pilots practise the five-minute QCT not only in day-to-day life but also during flight operations as a controlled rest strategy. The two-month QCT training effectively increases well-being and decreases perceived stress. Practising QCT in the flight deck improves pilots’ stress resilience and cognitive functions, subsequently improving human performance and aviation safety. This research can provide promising solutions to improve human performance and aviation safety. Furthermore, the AR and QCT applications have further practical implications for enhancing pilots’ non-technical skills in real operational scenarios. Also, the safety concerns of single pilot operations related to human capacity can be effectively addressed.
Braithwaite, Graham R. - Associate Supervisor
Keywords: human factors; non-technical skills; human-computer interaction; cognitive information processing; psychological well-being; stress resilience